Vegetative Growth, Harvesting Time, Yield and Quality of Mango (Mangifera indica L.) as Influenced by Soil Drench Application of Paclobutrazol (Bangladesh Journal of Agricultural Research, 2012)
The experiment was conducted during the fruiting season of 2005-06 to  investigate the effects of paclobutrazol in manipulating the harvesting time,  increasing yield and quality in mango (Mangifera indica) cv. BARI Aam-3  (Amrapali) plants at the BAU Germplasm Centre, FTIP, Department of  Horticulture, Bangladesh Agricultural University, Mymensingh. Paclobutrazol  at 2500, 5000, 7500, 10000 ppm, and control (water application) and two times  of application (15 October and 15 December) were included in the study as  treatments. Soil drench application of paclobutrazol at 10000 ppm and 7500  ppm on 15 October was more effective in suppressing vegetative growth i.e.  terminal shoot length, number of leaves and leaf area compared to control. Both  7500 ppm and 10000 ppm paclobutrazol applied as soil drench on 15 October  caused earlier panicle emergence by 19 days as well as harvesting by 15 days  compared with control. Applying paclobutrazol at 7500 ppm on 15 October  produced the highest number of fruits as well as yield per plant and the heaviest  fruit compared with the lowest yield in control. Paclobutrazol at 7500 ppm  applied on 15 October also resulted in higher edible portion, lower stone pulp  ratio and peel pulp ratio, longer shelf life, higher TSS, increased vitamin C,  lower titratable acidity, higher dry matter, reducing, non-reducing and total  sugar contents as compared to control plants. The present results suggest that the  application of paclobutrazol at 7500 ppm in October enhances yield and quality  in mango. DOI: http://dx.doi.org/10.3329/bjar.v37i2.11238 Bangladesh J. Agril. Res. 37(2): 335-348, June 2012